Xerostomia dan Penurunan Fungsi Rongga Mulut Pasien Lansia di RSGM Universitas Andalas - Gunawan Gunawan; Ivony Fitria; Desy Purnama Sari (Fakultas Kedokteran Gigi Universitas Andalas, 2023)
The number of elderly is predicted to continue to increase globally, including in Indonesia. According to data from the Central Statistical Authority, there has been an increase of 7 per cent in the percentage of elderly persons over more than a decade (2010-2021) to 10.82 per cent. The elderly age group is a highly susceptible group to a decrease in oral function caused by aging factors. Decreased oral function has a wide range of negative effects on the physical and psychological life of the elderly. Disorders perceived as a result of this condition will affect the nutritional intake of the elderly and also lead to a decrease in self-confidence, thus having a major impact on the quality of life of older people. The purpose of this study is to analyze the occurrence of xerostomy due to decreased function of the oral cavity of the elderly in UNAND RSGM. The research uses cross-sectional design, using total sampling techniques. A total of 30 elderly patients at UNAND's RSGM are expected to contribute to the study. Measurement of the state of decreased oral function is carried out with clinical examination, and subjective, then conducted interviews with questionnaires that have been tested validity and rehabilitation, in order to find out the determinant factors of decrease of oral function of elderly patients in UNAND RSGM. This research is in line with the UNAND Research Master Plan and Roadmap on the sub-theme of health and the results of this research will be able to be used as consideration of path determination of patient care plan and as educational material on the development of improvement of quality of life and health of the elderly. The results of the study showed a rate of xerostomy of 31.4%, a condition of hyposalivation of 14.3%, and there was no influence on the occurrence of xerostomy and hyposalyvation on the sociodemographic characteristics of elderly patients in the RSGM of the University of Andalas (p>0,05).   Keywords: aging, decreased function, oral cavity, xerostomia